Barriers and facilitators to incident reporting in mental healthcare settings: A qualitative study. Issue 3 (3rd December 2019) - Archer, Stephanie; Thibaut, Bethan I.; Dewa, Lindsay H.; Ramtale, Christian; D'Lima, Danielle; Simpson, Alan; Murray, Kevin; Adam, Sheila; Darzi, Ara
Accessible Summary: What is known on the subject?: The barriers and facilitators to incident reporting are becoming well known in general healthcare settings due to a large body of research in this area. At present, it is unknown if these factors also affect incident reporting in mental healthcare settings as the same amount of research has not been conducted in these settings. What the paper adds to existing knowledge: Some of the barriers and facilitators to incident reporting in mental healthcare settings are the same as general healthcare settings (i.e., learning and improvement, time and fear). Other factors appear to be specific to mental healthcare settings (i.e., the role of patient diagnosis and how incidents involving assault are dealt with). What are the implications for practice?: Interventions to improve incident reporting in mental healthcare settings may be adapted from general healthcare settings in some cases. Bespoke interventions for mental healthcare settings that focus specifically on violence and aggression should be co‐designed with patients and staff. Thresholds for incident reporting (i.e., what types of incidents will not be tolerated) need to be set, communicated and adopted Trust wide to ensure parity across staff groups and services. Abstract: Introduction: Barriers and facilitators to incident reporting have been widely researched in general health care. However, it is unclear if the findings are applicable to mental health care where care is increasingly complex. Aim: To investigate if barriers and facilitators affecting incident reporting in mental health care are consistent with factors identified in other healthcare settings. Method: Data were collected from focus groups ( n  = 8) with 52 members of staff from across West London NHS Trust and analysed with thematic analysis. Results: Five themes were identified during the analysis. Three themes (a) learning and improvement, (b) time and (c) fear were consistent with the existing wider literature on barriers and facilitators to incident reporting. Two further themes (d) interaction between patient diagnosis and incidents and (e) aftermath of an incident—prosecution specifically linked to the provision of mental health care. Conclusions: Whilst some barriers and facilitators to incident reporting identified in other settings are also prevalent in the mental healthcare setting, the increased incidence of violent and aggressive behaviour within mental health care presents a unique challenge for incident reporting. Clinical implications: Although interventions to improve incident reporting may be adapted/adopted from other settings, there is a need to develop specific interventions to improve reporting of violent and aggressive incidents.